Employee perceptions of flexible working agreements: An investigation of the dark sides of teleworking - Nyberg, Henri Juhana Aleksanteri (My University, 2019)
An increasing amount of work these days can be done digitally. Furthermore, employees are increasingly working as part of virtual teams where their coworkers can be in a different city or even in a different country. These things are among the many drivers that have made an increasing number of workers and companies to start using flexible working agreements to give employees some autonomy to choose when and where they work. There has been much research about the positive effects of flexible work both for the employee and the organization. However, one can already see that extensive digital communication and 24/7 connection to social media have had some negative effects on people’s lives. It is likely that these negative effects can manifest themselves in peoples’ working life as employees are moving away from the workplace to more autonomous and increasingly digital workspaces. The aim of this thesis is to explore the negative outcomes, sometimes referred to as ‘the dark outcomes’, of flexible work. The thesis first explores the pros and cons of flexible work for the employee and organization as identified in previous literature. The empirical part of the research focuses on employee perceptions of flexible work, and on shedding light on employees’ experiences of potential negative effects of teleworking. This is a qualitative study. The empirical data was collected by interviewing ten employees who had various types of FWA contracts with an option or requirement for telework. The interviews were structured, with everyone being asked the same questions. The sample consists of people working in China and Finland, and the respondents/interviewees are engaged in white collar work. The results were analyzed against the theory regarding FWAs. All of the individuals interviewed for this study felt rather positive about their FWAs and would not want to decrease the amount of flexibility their organization allows for them. However, some negative consequences were discovered, such as difficulties of switching off from work as one was technically “on call” even outside of traditional office hours. Employees also felt that it was sometimes easier to explain or discuss topics when they were face to face with their colleagues in the office, rather than working digitally from their home or some other non-traditional working space. Finally, many employees in this study had experienced technical difficulties when trying to connect to their employer networks remotely and had lost working hours or even days due to the fact of the internet or digital tools not working correctly when they were teleworking.
Keywords: Flexible working agreement; dark outcomes; telework; employee perception; fi=Master's Degree Programme in International Business|